Direct-supply chilled-water radiant-floor cooling system coupled with an earth‒air heat exchanger system: A case study in a building - Jiaming Yang; Huiqing Cao; Zhenwei Wang; Yue Liu; Wei Song; Jiankai Dong (Case Studies in Thermal Engineering)
To date, the use of shallow geothermal energy to directly cool and dehumidify a building in summer via a direct-supply chilled-water radiant-floor cooling (DS-RFC) system coupled with an earth‒air heat exchanger (EAHE) system has not been investigated. In this study, a physical test was performed in a real-world application room, where the cooling and dehumidification characteristics of DS-RFC and EAHE systems were individually studied to evaluate their application potential. The changes in the indoor air temperature and humidity and in the soil temperature when the two systems were operated independently were quantitatively analyzed. Additionally, the effects of the coupled DS-RFC/EAHE system on the indoor environment were evaluated for three air-supply inlet locations. The results showed that the DS-RFC system had a superior cooling effect but almost no dehumidification ability; the change in the humidity ratio was less than 2.00 g/kg. The EAHE system had a superior dehumidification effect, where the change in the humidity ratio exceeded 5.00 g/kg. When the DS-RFC system was operating, different air-supply inlet positions significantly affected the change states of the indoor-air state parameters. The indoor temperature was primarily concentrated at 25–27 °C, and the relative humidity was 83–88 %. This study provides rational support for a building cooling model in which a DS-RFC system coupled with an EAHE system is supplied directly by shallow geothermal energy in summer.